Pengembangan Sensor Rasa Asin Impedimetrik Menggunakan Interdigitated Electrode Termodifikasi Membran Lipid 1-Hexadecanol - Annisa Wachida Qurrata A'yun (Department of Physics Universitas Gadjah Mada, 2025)
This study proposes a method for evaluating salty taste using an impedimetric sensor based on an interdigitated electrode modified with a 1-hexadecanol lipid membrane. To improve the selectivity of the saltiness sensor, we optimized the total concentration of lipid/PVC/plasticizer in a THF solvent. The impedance response of the sensor was measured in a frequency range of 1 Hz - 100 kHz, then the feature extraction is performed based on frequency that has the greatest influence on the taste classification. From feature extraction, it is found that low frequency has a significant contribution to the taste classification so that the frequency range 1-108 Hz is taken to be analyzed using principal component analysis (PCA) and linear discriminant analysis (LDA) to determine the sensor's membrane performance on saltiness selectivity. Then, the silhouette coefficient score was calculated and compared between sensors to evaluate their saltiness selectivity. Our results show that the best lipid membrane concentration for sensor coating is 9 w/v%, with a silhouette coefficient score is 0.75 for PCA and the accuracy obtained from k-fold cross-validation using LDA is 100%. Furthermore, we used the optimized lipid membrane sensor to measure salt solution concentrations in water to test the sensor's sensitivity. Our results demonstrate that the impedance response decreases as the NaCl concentration increases.Keywords : taste sensor, lipid membrane, interdigitated electrode, impedimetric